HUBUNGAN KECERDASAN INTERPERSONAL DENGAN KEPERCAYAAN DIRI PADA ANAK USIA 5-6 TAHUN DI TK AL-FAJAR KECAMATAN TAMPAN PEKANBARU - Fadillah, Melda Aulia; Zulkifli N, Zulkifli N; Risma, Devi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The purpose of this research is to know the correlation between interpersonal intelligence and self-confidence on children 5-6 years old at Al-Fajar Kindergarten Tampan Pekanbaru district. The population of this research is 40 students 5-6 years old at Al-Fajar Kindergarten Tampan Pekanbaru district. Because the number of the population is small, so all of them became the sample of the population. The method used in this research was quantitative correlation to know the correlation between interpersonal intelligence and self-confidence. The technique of collecting the data is observation. The technique of data analysis is using product moment correlation technique with SPSS for windows version 17 program. Based on the result of the hypothesis test there is a significant positive correlation between interpersonal intelligence and self-confidence on children in 5-6 years old at Al-Fajar Kindergarten Tampan Pekanbaru district. This can be known from the value of the correlation coefficient of rxy =0,776 and significance level 0,000<0,05. The level of correlation between interpersonal intelligence and self-confidence included in the strong category with the value of determinant coefficient is equal to KD = rÂ² x 100% = 60,2%, it means that interpersonal intelligence gives effect of 60,2% to self-confidence.Key Word: Self-Confidence, Interpersonal Intelligence